Osteosynthesis of Ideberg type III glenoid fracture with retroclavicular cannulated percutaneous screw - Tonelli, Filippo; Sani, Giacomo; Bartolini, Saverio; Mugnaini, Marco (Lo Scalpello - Journal, 2021)
In this article we report a 74 year old patient with Ideberg-type III fracture who was treated with indirect reduction and fixation. The patient was a sportive biker who suffered from a high energy trauma (road accident). X-ray revealed a scapula fracture, and only after a CT-Scan we could confirm the fracture type (Ideberg-type III glenoid fracture). The patient was operated and re-evaluated at follow-up. During the surgery we prefered not to access intra-articular due to the low joint involvement. He was able to resume his daily activities at two months postoperatively. At three months ASES Score was 91.5; Constant Score was 71 (vs 96 of unaffected arm). The patient revealed to be satisfied with the treatment, moreover the clinical results are encouraging in view of further improvements in the following months.